In vitro: anticancer effect of oily and methanolic extracts of Al-Zahdi (Phoenix dactylifera L.) from dry dates and leaves on AMN3, Hela and Ref cancer cell cultures - Saadia Saleh Mehdy Al-Zeiny; Kifah Jabbar Alyaqubi; Duraid Abdul Hadi Abbas (Kufa Journal for Veterinary Medical Sciences, 2022)
The antioxidant and anti-tumor effects of extracts from various herbs and medicinal plants were measured using various in vitro and in vivo methods. The current study investigates and compare the anticancer effects of the two palm part extracts against cancer cell line in cultured cell line of AMN3, Hela and Ref. The results showed a concentration dependent inhibitory cytotoxic effects during 72 hrs of exposure for methanolic and oily crude extracts of date and leaves on AMN3, Hela and Ref cell lines. The highest significant effect of both dry date and leave methanolic extracts were achieved at concentration 2500 μg/ ml that causing highest growth inhibition percentage (GIP) of (73.3 %, 66.4%) for AMN3 and (76.7 %, 55.4%) for Hela respectively. The concentration 5000 μg/ ml showed nearly less effect after 72 hrs exposure. Both methanolic extracts tested concentrations didn’t cause   any inhibitory effect on the REF cell line. The effect of date and leaves oily extracts at different concentrations caused on tumor Cell Line AMN3, Hela and Ref highly significant in difference at exposure periods 72   hrs for concentrations gradient ranged from (15.62- 250 μg/ml). The concentration 125 µg/ml showed higher inhibition percentage compared to the higher concentration of 2500 µg/ ml causing   on AMN3 (85.1%, 66%), Hela (79.1%, 77%), and Ref (76%, 61.7%), respectively.  Plateau were noticed for all highest palm extracts concentrations GIP effect on all cell line cultures. The study concluded that the superiority of oil extract for both date and leave over alcoholic extracts one in inhibition of in vitro the same cell lines AMN3, Hela, Ref.